2015
DOI: 10.1515/hukin-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nordic Walking and Water Aerobics Training on Body Composition and the Blood Flow in Lower Extremities in Elderly Women

Abstract: Nordic walking and water aerobics are very popular forms of physical activity in the elderly population. The aim of the study was to evaluate the influence of regular health training on the venous blood flow in lower extremities and body composition in women over 50 years old. Twenty-four women of mean age 57.9 (± 3.43) years, randomly divided into three groups (Nordic walking, water aerobics, and non-training), participated in the study. The training lasted 8 weeks, with one-hour sessions twice a week. Dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
10

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
15
0
10
Order By: Relevance
“…Beraldo et al 14 described the possibility of using PPG in assessing the vascular bed. Similar studies were performed by Jasinski et al 2 in females with a diagnosed peripheral arterial disease. The authors observed that, after 8 weeks of physical activities, the quality of venous blood flow in the vessels had improved.…”
Section: Discussionsupporting
confidence: 82%
“…Beraldo et al 14 described the possibility of using PPG in assessing the vascular bed. Similar studies were performed by Jasinski et al 2 in females with a diagnosed peripheral arterial disease. The authors observed that, after 8 weeks of physical activities, the quality of venous blood flow in the vessels had improved.…”
Section: Discussionsupporting
confidence: 82%
“…Four studies reported that walking was ‘self-paced’14 17 21 22 and seven studies noted that walking intensity was at a ‘brisk pace’ 13 16 33 34 41 42 48. In addition, two studies measured the intensity as walking speed44 50 and one study as HR,43 MET,46 RPE47 and ventilator threshold49 each.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome measures were aerobic fitness expressed as VO 2max (mL/kg·min), body mass (kg), body fat (%), BMI (weight in kilograms divided by height in metres squared), waist circumference (cm), waist-to-hip ratio, systolic and diastolic blood pressure (mm Hg), total cholesterol (mmol/L), high-density lipoprotein (HDL) cholesterol (mmol/L), low-density lipoprotein (LDL) cholesterol (mmol/L), triglycerides (mmol/L) and fasting glucose (mmol/L). Outcomes for insulin resistance and inflammation-related serum cytokines,45 blood flow in lower extremities,46 arterial stiffness,48 postural stability,42 bone mineral density42 and biomarkers of endothelial function49 were not included in the meta-analyses because of insufficient number of comparisons (<10) (see Higgins and Se54). …”
Section: Methodsmentioning
confidence: 99%
“…The hand search of the references of all relevant studies identified one relevant study (Arslan, 2011). After removal of duplicates and exclusion of studies based on predetermined criteria, the final sample included 9 RCTs (Araújo et al, 2015;Arslan, 2011;Jasiński et al, 2015;Kantyka, Herman, Roczniok, & Kuba, 2015;Kin-Isler & Kosar, 2006;Melam et al, 2016;Nagle et al, 2007;Novaes et al, 2014;Park et al, 2003) and 5 uncontrolled clinical trials (Duzova et al, 2018;Hallage et al, 2010;Pilch et al, 2017;Ruiz-Montero, Castillo-Rodriguez, Mikalacki, Nebojsa, & Korovljev, 2014;Said, Lamya, Olfa, & Hamda, 2017), the overview of which is shown in Table 2. The final sample included studies published primarily in Europe, Asia, North and South America.…”
Section: Resultsmentioning
confidence: 99%